Protective role of cardiac progenitor cell-derived-exosomes in a new human model of ageing-induced cardiac dysfunction. (10th June 2022) - Lazzarini, E; Lodrini, AM; Bolis, S; Arici, M; Vagni, S; Panella, S; Rendon Angel, A; Torre, T; Vassalli, G; Ameri, P; Altomare, C; Rocchetti, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Velux Stiftung Background: Ageing of cardiomyocytes (CM) involves structural and functional adverse remodelling that finally could result in heart failure (HF) insurgence, which incidence rise along with age (1). Current medical therapies for HF may not always be tolerated in elder patients(2). Having shown that cardiac progenitor cells (CPCs) secrete nanoparticles named exosomes (EXO) enriched of cardioprotective factors(3, 4), we are exploring EXO's capacity to ameliorate senescence-derived modification into CMs. However, human models of in vitro cardiac aging are currently missing(5). Aim: This study exploits CMs derived from human induced pluripotent stem cells (hiPSCs) as an in vitro model for cardiac senescence, that will be used as platform to characterize mechanisms involved in cardiac ageing and to test protective effect of CPC-derived EXO. Methods: Patient-derived CPCs were reprogrammed into hiPSCs and subsequently expanded and differentiated into cardiomyocytes (hiPSC-CMs). Senescence-like phenotype was induced by short exposure (3 hours) to doxorubicin (DOX) at sub-lethal concentration (0.2 µM), followed by washing and medium change. Following DOX exposure, cells were exposed to EXO, derived from the purification of conditioned culture media of CPCs using an ultracentrifugation-based isolation method and quantified and sized using a NTA counter. Senescence induction was highlighted by protein and gene expression analysis and senescence-associated b-galactosidase (SA-β-gal) assay.Electrical activity of hiPSC-CMs was evaluated recording extracellular field potentials through multi-microelectrode arrays (MEA) and by single cell patch clamp. Metabolic features were analysed with western blot, real time RT-PCR and specific biochemical assays. Results: DOX treatment in hiPSC-CMs induced senescence, as confirmed by activation of p21 and p16 pathways and increasing of SA-β-gal staining as compared to untreated cells (CTR). Biochemical and gene expression analysis revealed an increased ROS production and a reduction in mitochondrial potential, which drives a strong decrease in the ATP/AMP ratios. Real Time PCR analysis reveal an increased transcription of molecules related to the senescence associated secretory phenotype in DOX-CMs. Moreover, DOX-CMs showed impaired Ca++ handling, prolonged multicellular QTc and single cell APD, with increased APD variability and delayed afterdepolarizations (DADs) incidence in comparison to CTR. EXO treatment mitigated the senescent phenotype induced by DOX, as shown by a decreased ROS induction, higher mitochondrial potential which drives a restored ATP/AMP ratio. Furthermore, DOX-induced QTc prolongation was prevented by EXO treatment. Conclusion: Our hiPSC-CMs based cellular model recapitulates the phenotype of aged CMs in terms of senescence markers, electrical and metabolic proprieties. CPC-derived EXOs limit age-related modifications, highlighting the cardioprotective role of small molecules released by EXO.